Consumer Behavior toward the Use of Credit Cards: The Empirical Evidence from Iraq - Ahmed, Amanj Mohamed (IAIN Surakarta, 2020)
Credit card is a payment tool in the modern world and it is being called the plastic money. In Iraq and especially in Kurdistan region, the credit card utilization now is appealing to be more attractive. To address this issue, the present study sheds some light on the impact of credit cards on the consumer behavior and the benefits of credit cards for people of Kurdistan, Iraq. The data were obtained from 40 participants consisting of academicians in the related field, managers of banks, and credit card users by means of questionnaires. A range of variables that agreed to demographic information, such as level of education, gender, and income, were also considered. Drawing on chi-square and modeling analysis, the results portrayed a positive relationship between the costumer information and their behavior in using credit cards. The results of this study further suggest that since people in Kurdistan region of Iraq would like to apply credit cards in all aspects of life, the financial institutions should provide accessible information and valuable services. All in all, from this study it is implied that the â€œplastic moneyâ€ makes a revolution in banking industry across the world and nowadays electronic banking becomes familiar to the world.